Developing Tactical Training of Student Volleyball Players - Xudoyqulovich, To`laganov Rustam (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article, volleyball belongs to the types of sports games and differs from them in its essence and content. It is shown that it is the only vehicle that allows to carry out all technical and tactical activities.